The effect of rare-earth nanoparticles on drug delivery - Li, Linda Shi Wen (2011)
Cancer, being one of the leading causes of death worldwide, has received much attention for the past century. Utilizing nanoparticles as a drug delivery vehicle has become widely popular in cancer therapy. However many classifications of nanoparticles, despite their high efficiency in drug delivery, have been known to have high cytotoxic levels. In recent years, rare-earth nanoparticles were brought to attention, as these up-conversion particles not only facilitate imaging, but have also reduced cytotoxic effects on cells.